Governance in Nottingham and Stuttgart: a comparative case study of power, inequality and sustainability - Keding, Hannah (2020)
Various environmental, economic and social practices in democratic capitalist countries like Germany and the UK cannot be sustained long-term without undermining their own foundations. Understanding what may facilitate more sustainable ways of living together is therefore paramount. The case study at hand makes an original contribution to this aim by comparing urban governance in Nottingham (UK) and Stuttgart (Germany) as two exemplars of capitalist variation – with different consequences for how capitalism’s unsustainabilities play out.